Parental Stress of Preschool Children With Generalized Anxiety or Oppositional Defiant Disorder - Manti, Filippo; Giovannone, Federica; Sogos, Carla (Frontiers in Pediatrics, 2019)
Abstract Background: Generalized anxiety and oppositional defiant disorders are among the most common psychopathological disorders in preschool children. We investigated the symptom rate and perception of the child’s disorders in parents of preschool children with generalized anxiety disorder (GAD) or oppositional defiant disorder (ODD). Methods: The parents of preschool children (mean age 54.35 months, SD±11.60) with ODD, GAD or typical development (TD) filled the Symptom Check List-90-Revised (SCL-90-R) and the Child Behavior Checklist- 1½-5 (CBCL 1 ½ 5). Parents and children’s diagnoses were determined by clinical assessment. Results: The parents of children with ODD reported symptoms rate higher than parents of children with GAD or TD on most of the SCL-90-R (Global Severity Index of mental distress, p=.010; Somatization, p=.002; Paranoid Ideation, p<.000; and Phobic Anxiety scales, p=.030). Conclusions: On the CBCL scales, the parents of the ODD group overestimated children's problems, while parents of children with GAD reported mainly children’s emotional difficulties. Parents of children with ODD seem to be psychologically more vulnerable than parents of children with GAD. Parenting programs might be tailored considering the child’s diagnosis and family functioning.